Penggunaan Podcast Redaksi Siniar LPM Dinamika Sebagai Media Informasi Akademik Mahasiswa - Paradita, Ella; Ritonga, Muhammad Husni; Matondang, Muhammad Alfikri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The objective of this study is to enhance comprehension of how the podcast LPM Dynamics Editorial Synopsis as an academic information medium for students. Qualitative descriptive methods are used in this study to observe the use of media podcasts. In data collection, researchers conduct interviews and analyses. Researchers divide key informants and supporters in the data collection process. Key informants are individuals who understand research issues in detail and are willing to be interviewed. The podcast manager, LPM Dynamika's Siniar Editor, provides important information here. To select a supportive informant, the researchers also used purposive urposive sampling. The researchers used eight UIN SU student informants, the study was conducted at the Islamic State University of North Sumatra. The study's findings suggested that students liked the podcast LPM Dynamika Sinyar Editorial because of its interesting message delivery. LPM Dynamics Podcasts provide an extensive array of accessible information. The Podcast is considered effective as an academic information medium for students because of its excellence that is accessible at any time.